Childhood Predictors of Written Expression in Late Adolescents with 22q11.2 Deletion Syndrome: A Longitudinal Study - Hamsho, Narmene (J Intellect Disabil Res, 2017)
BACKGROUND: 22q11.2 Deletion Syndrome (22q11DS) is the second most prevalent genetic syndrome and has a characteristic academic and behavioural phenotype. The primary objective of the current study was to examine the childhood predictors of written expression achievement in adolescents with 22q11DS. Written expression is an important skill that can impact an individual’s overall academic performance, potentially resulting in increased levels of stress and exacerbation of psychiatric symptoms. METHODS: A total of 119 participants were included in this study. Sixty-nine late adolescents with 22q11DS and 50 controls (consisting of a combined sample of 23 unaffected siblings of youth with 22q11DS and 27 community controls) participated in a 6-year longitudinal research project and received neuropsychological test batteries every 3 years. The Written Expression subtest of the Wechsler Individual Achievement Test–2(nd) edition (WIAT-II) was the primary outcome measure in the current project. RESULTS: Findings indicated differences in childhood predictors of adolescent written expression between participants in the 22q11DS group and participants in the control group. Whereas childhood verbal IQ scores predicted adolescent written expression for participants in the control group, childhood executive function and language skills were unique predictors of adolescent written expression in individuals with 22q11DS. CONCLUSIONS: Childhood predictors of late adolescent written expression in 22q11DS differ in meaningful ways from predictors in the non-22q11DS population. These results offer some guidance on the underlying factors that may be useful to consider when developing written expression interventions for children with 22q11DS.